Interpretasi Kasih Ibu dalam Cerpen Al-Hubbu Al-Kabir Karya Abdullah Muhammad Abdul Mu’thi: Analisis Semiotika Charles Sander Peirce - Tsabita, Hania Nuha; Nurfadhilah, Incha; Assholihy, Akram Sajid; Sudarmawan, Habib Muharrom (Prosiding Konferensi Nasional Bahasa Arab, 2024)
Semiotic theory developed by Charles Sanders Peirce can be applied to analyze various forms of literary works, one of which is the short story. This research uses qualitative text analysis methods to examine the semiotics of the short story entitled Al-Hubbul-Kabir by Abdullah Muhammad Abdul Mu'thi. Great love does not only apply to lovers. Through this short story, readers are given an interpretation of the magnitude of a mother's love for her child based on the results of analysis by implementing Charles Sanders Peirce's semiotic theory. Even though it is written in fable form, short stories can provide an illustration of sacrifice, proof of love and deep sincerity of a mother.تطبيق النظرية السيميائية التي وضعها تشارلز ساندرز بيرس لتحليل أشكال مختلفة من الأعمال الأدبية، أحدها القصة القصيرة. يستخدم هذا البحث أساليب تحليل النص النوعي لفحص سيميائية القصة القصيرة بعنوان الحبول الكبير لعبد الله محمد عبد المعطي. الحب الكبير لا ينطبق فقط على العشاق. من خلال هذه القصة القصيرة، يتم إعطاء القراء تفسيرًا لحجم حب الأم لطفلها بناءً على نتائج التحليل من خلال تطبيق نظرية تشارلز ساندرز بيرس السيميائية. على الرغم من أنها مكتوبة في شكل أسطوري، إلا أن القصص القصيرة يمكن أن تقدم مثالاً على التضحية ودليلًا على الحب والإخلاص العميق للأم. والاستنتاجات الرئيسية. مستخلص البحث مكتوب باللغة الإنجليزية والعربية. يتم تقديم مستخلص البحث في فقرة تحتوي على 100-150 كلمة. يجب ألا يكون هناك أخطاء إملائية وقواعد وتعبيرات في اللغة المستخدمة.